2022
DOI: 10.3390/ijms23169334
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Probiotic Bifidobacterium animalis subsp. lactis HN019 in Oral Diseases

Abstract: The oral cavity is one of the environments on the human body with the highest concentrations of microorganisms that coexist harmoniously and maintain homeostasis related to oral health. Several local factors can shift the microbiome to a pathogenic state of dysbiosis. Existing treatments for infections caused by changes in the oral cavity aim to control biofilm dysbiosis and restore microbial balance. Studies have used probiotics as treatments for oral diseases, due to their ability to reduce the pathogenicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 94 publications
0
10
0
1
Order By: Relevance
“…The trend was reversed upon administration of the high‐dose GTE, as it fostered the proliferation of Lactobacillus and Bacillus while concurrently suppressing Burkholderiales . Researches showed that Lactobacillus and Bacillus were generally gram‐positive bacteria, whereas the Burkholderiales order contained four families of gram‐negative bacteria (Araujo et al., 2022; Sim et al., 2010; Zhao & Kuipers, 2016). Figure 5d displays the functional predictions of the oral microbiota via analyzing the cluster of orthologous group database.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The trend was reversed upon administration of the high‐dose GTE, as it fostered the proliferation of Lactobacillus and Bacillus while concurrently suppressing Burkholderiales . Researches showed that Lactobacillus and Bacillus were generally gram‐positive bacteria, whereas the Burkholderiales order contained four families of gram‐negative bacteria (Araujo et al., 2022; Sim et al., 2010; Zhao & Kuipers, 2016). Figure 5d displays the functional predictions of the oral microbiota via analyzing the cluster of orthologous group database.…”
Section: Resultsmentioning
confidence: 99%
“…Oral microorganisms, such as Streptococcus mutans and Aggregatibacter actinomycetemcomitans , contributed to the pathogenesis of dental caries, periodontitis, and other oral diseases, and were associated with laryngeal cancer (Li et al., 2022; Peng et al., 2022; Simón‐Soro & Mira, 2015; Wang et al., 2019). In addition, every day about 600 mL of saliva rich in oral microbe is swallowed through the aerodigestive tract (Araujo et al., 2022). Imbalances in the oral microbiota may lead to disruption of the gut microbiome, which in turn induced inflammation and systemic changes (Iwauchi et al., 2019; Xu et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Through its metabolism, it can produce a bene cial metabolite called Nmethylserotonin, which has been shown to promote weight loss, reduce fat accumulation, and enhance intestinal transit (Han et Bi dobacterium animalis belongs to the Bi dobacterium genus, which is widely recognized as a physiologically bene cial bacterium with various important functions for human health. These functions include acting as a biological barrier, providing nutritional bene ts, exhibiting anti-tumor effects, enhancing immune activity, improving gastrointestinal function, and promoting anti-aging effects (Araujo et al 2022). Supplementation with Bi dobacterium has been shown to prevent obesity and hyperlipidemia in mice with diet-induced obesity.…”
Section: Discussionmentioning
confidence: 99%
“…A growing amount of evidence has been showing that Lactobacillus and Bifidobacterium strains can alter subgingival biofilms and modulate the immunoinflammatory response, leading to improved periodontal health [ 138 , 139 , 140 ]. Very recently, Wu and collaborators [ 140 ] showed, through metagenomic sequencing, that Lactobacillus paracasei L9 and Bifidobacterium animalis A6 proportionate a significant modification on the taxonomic composition of the subgingival microbiome, by reducing the relative proportions of pathogenic bacterial genera, such as Streptococcus , Fusobacterium , Veillonella , and Escherichia ; overall, they recommended additional research to be conducted to explore the promising use of these two probiotics as prophylactic agents for periodontitis.…”
Section: Current Alternatives To Antibiotics To Prevent and Treat Ora...mentioning
confidence: 99%